Functional Imaging with Higher-Dimensional Electrical Data Sets. (15th November 2018) - De Wolf, P.; Huang, Z.; Pittenger, B.; Dujardin, A.; Febvre, M.; Mariolle, D.; Chevalier, N.; Mueller, T.
Abstract: Abstract: AFM-based nanoelectrical modes have numerous applications in fields ranging from semiconductors to biology. The data produced have traditionally been in the form of a 2D map, generated in contact mode, with a single electrical data point per XY location. Electrical ramps or spectra would be generated at a few, carefully selected locations. This article discusses a new approach to nanoelectrical imaging that creates an electrical data cube and a correlated nanomechanical data cube while operating at normal imaging speeds. This approach avoids contact mode imaging, thus extending electrical measurements to soft and fragile samples and improving measurement consistency. Moreover, this is a general approach that is applicable to most nanoelectrical modes and applications.